2017
DOI: 10.1002/ar.23688
|View full text |Cite
|
Sign up to set email alerts
|

Inversed Expression Patterns of S100A4 and E‐Cadherin in Cervical Cancers: Implication in Epithelial–Mesenchymal Transition

Abstract: Cervical cancer/CC is the third commonest female malignancy worldwide. The aggressive growth and distal metastases are the leading causes of CC mortality, which is largely due to epithelial-mesenchymal transition/EMT. Fibroblast specific protein S100A4 promotes cancer metastasis and epithelial type cadherin/E-cadherin play pivotal roles in cell-cell and cell-extracellular matrix interaction. Therefore, the expression patterns of S100A4 and E-cadherin reflect statuses of EMT of carcinoma cells. However, S100A4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…Together with our miR-9-5p inhibition data in SiHa and CaSki, this indicates that miR-9-5p also targets CDH1 in cervical SCC, even though the effect of miR-9-5p on TWIST1 was more pronounced. In HeLa, where miR-9-5p expression is low, low and undetectable levels of CDH1 might therefore be mediated by high levels of TWIST1 rather than miR-9-5p [59]. In support of that and similar to our findings, Zhang et al observed no effect of miR-9-5p on CDH1 expression in HeLa [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Together with our miR-9-5p inhibition data in SiHa and CaSki, this indicates that miR-9-5p also targets CDH1 in cervical SCC, even though the effect of miR-9-5p on TWIST1 was more pronounced. In HeLa, where miR-9-5p expression is low, low and undetectable levels of CDH1 might therefore be mediated by high levels of TWIST1 rather than miR-9-5p [59]. In support of that and similar to our findings, Zhang et al observed no effect of miR-9-5p on CDH1 expression in HeLa [22].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, CDH1 has also been established as a direct target of miR-9-5p in a multitude of human cancers [12,16,[37][38][39][40][41]. In cervical cancer, downregulation of CDH1 has been observed [58][59][60]. Together with our miR-9-5p inhibition data in SiHa and CaSki, this indicates that miR-9-5p also targets CDH1 in cervical SCC, even though the effect of miR-9-5p on TWIST1 was more pronounced.…”
Section: Discussionsupporting
confidence: 71%
“…To summarize, in line with previous observations that in normal and benign lesions, S100A4 is restricted to a few stromal fibroblasts and inflammatory cells [42], while both tumor and stromal cells secrete the protein in malignant tumors [42,43], we observed a continuous rise in S100A4 from subnormal, epithelioid, sarcomatoid non-tumorigenic mesothelial cells to MM cell lines. The increased abundance of this protein in invasive versus non-invasive MM cell lines and invasive versus non-invasive MM tumors was consistent with reports of its higher expression in the peripheral leading edge of breast cancer [43], non-small-cell lung cancer (NSCLC) [44], and gain of S100A4/loss of membrane E-cadherin in cervical cancer with an unfavorable prognosis [8]. The parallel between S100A4 and fibronectin is also of interest, as the continuous increase in protein abundance between subgroups Sbnl, PNep, and PNint, and the difference between sarcomatoid and epithelioid preneoplastic rat mesothelial cell lines suggest a relationship with the Wnt signaling pathway [45].…”
Section: Discussionsupporting
confidence: 88%
“…The contribution of S100A4 to the EMT process has been demonstrated in patients, being particularly highly expressed in the peripheral leading edge of breast cancer [6], and experimentally in a context of transformation of a non-metastatic human prostate cancer cell line, which leads to the cancers' acquiring invasive properties [7]. The combined gain of S100A4 and loss of membrane E-cadherin in cervical cancer tends to confirm its link with an unfavorable prognosis [8]. Moreover, the role of this biomarker as a central node in a molecular network controlling stemness and EMT has been reported in one of the most aggressive tumors, glioblastoma [9], providing the initial parts of an answer to the question of the relationship between these two processes [10].…”
Section: Introductionmentioning
confidence: 92%
“…Next, our study demonstrated that silencing of S100A4 restrained the viability, migration, and invasion of rCSCs in virto. 8 , 37 , 38 The promotion in cancer cell migration and invasion mediated by overexpression of S100A4 has been suggested in several human cancers, such as cutaneous squamous cancer, 39 hepatocellular carcinoma, 40 and squamous cell laryngeal cancer. 41 Our study suggested that S100A4 also modulated those capacities of rCSCs, through which S100A4 silencing was conducive to wound repair.…”
Section: Discussionmentioning
confidence: 99%